Using A Graphing Calculator To Graph Linear Equations y MX + B Slope-Intercept Form Graph Table (2nd Graph) X-Y Table Find Intercepts Find Points
Using A Graphing Calculator To Graph Linear Equations y MX + B Slope-Intercept Form Graph Table (2nd Graph) X-Y Table Find Intercepts Find Points
Using A Graphing Calculator To Graph Linear Equations y MX + B Slope-Intercept Form Graph Table (2nd Graph) X-Y Table Find Intercepts Find Points
y = mx + b slope-intercept
form
graph
table (2nd graph) x-y table
find intercepts
find points
13. Systems of linear equations
Definitions:
System of linear equations – consists of 2 or
more linear equations
(lines)
x + 2(3x + 2) = 11 Distribute
x + 6x + 4 = 11 Combine like terms
7x + 4 = 11 Subtract 4 from both sides
-4 -4
7x = 7 Divide both sides by 7
7 7
x=1 Still need to find y, substitute
---------------------------- x into either original equation
y = 3x + 2 and solve for y
y = 3(1) + 2
y=5 Answer: (1, 5) Check answer
Example 2: x – 2y = -6
4x + 6y = 4 .
1. Solve 1st equation for x x – 2y = -6
+2y +2y
x = 2y – 6
2. Substitute (2y-6) into 2nd
equation for x. 4(2y – 6) + 6y = 4
3. Distribute 8y – 24 + 6y = 4
4. Combine like terms 14y – 24 = 4
5. Add 24 to both sides +24 +24
14y = 28
6. Divide both sides by 14 14 14
y=2
----------------------------------------------------------------------
Continued on next slide
Only have 1 coordinate for the point of intersection, so….
7. Substitute y value into
either original equation 4x + 6y = 4
and solve for x 4x + 6(2) = 4
4x + 12 = 4
-12 -12
4x = -8
4 4
x = -2
4x + 3y = 2 → 4x + 3y = 2
-1(5x + 3y = -2) → -5x – 3y = 2 Now add
-1x = 4
-1 -1
x = -4
Find 2nd variable: 4(-4) + 3y = 2
-16 + 3y = 2
16 16
3y = 18
3 3
y=6 Answer: (-4, 6)
Example 3:
8x – 4y = -4 → 8x – 4y = -4
4y = 3x + 14
-3x -3x → -3x + 4y = 14
5x = 10
5 5
x=2
--------------------------------------------------------------------
8(2) – 4y = -4
16 – 4y = -4
-16 -16
-4y = -20
-4 -4
y=5 Answer: (2, 5)
Homework: p. 447- 448 #3 – 21 odds, 25
16. Solving systems by elimination
6x + 5y = 19 → 6x + 5y = 19
-3(2x + 3y = 5) → -6x – 9y = -15 Add
- 4y = 4
-4 -4
y = -1
2x + 3(-1) = 5
2x - 3 = 5
3 3
2x = 8 x=4 (4, -1)
2 2
Example 2: 4x + 5y = 35
-3x + 2y = -9
Example 4: 2x + 5y = 1
3x + 10y = -3
Example 5: 3x – 7y = 5
9y = 5x + 5
Use substitution.
x – 2(½x + 2) = -4
x – x – 4 = -4
-4 = -4